التحذياث التي تىاجه هعلوي البرًاهج )A2 )للغت العربيت في ثاًىياث جسر المور في تٌويت ههاراث تعلن المرى الحادي والعشريي لذي طلبت اللغت العربيت - Nidhoimi, Said Omar Antoine; Badrasawi, Kamal J I; Ahmed Mohamed, Ismaiel Hassanein; Mamat, Arifin (2019)
This qualitative study aimed to diagnose the challenges facing teachers of the (A2) program for the Arabic language in developing 21st century learning skills among students of the Arabic language in Comoros high schools. The 21st century imposes an interest in acquiring students the skills that can help them solve their learning problems, prepare for work and live in this 21st century, the ability to innovate, innovate and collaborate in their practices rather than compete, and to be able to adapt to the rapid technological change and development of a modern society. This research dealt with semi-organized personal interviews from six teachers for this program in one of the islands, and the researcher interviewed them one by one. The content of the interviews was analyzed, and the topics were extracted. This research is divided into two sections. The first section deals with the effects that impede the application of 21st century learning skills among Arabic language students from the teachers' point of view. Administratively, there is a problem in the curriculum and teaching methods, weak response of students towards learning the Arabic language, while the second section deals with the suggestions of teachers on how to develop the application of skills among students of the Arabic language from the perspective of teachers which are: Raising interest in Arabic (2) Providing modern teaching aids (3) Raising students' desire towards learning Arabic.